Discursive And Pragmatic Features Of Proverbs Expressing Politeness In English And Uzbek Languages Introduction - Shamuradova Naima Muxtarovna (Genius Journals, 2025)
This article explores the discursive and pragmatic features of proverbs expressing politeness in English and Uzbek languages. Proverbs are examined as culturally specific linguistic units that encode norms of social behavior, etiquette, and moral values. The study applies the theoretical frameworks of Brown and Levinson’s politeness theory, Leech’s principles of pragmatics, and Grice’s cooperative maxims to reveal how politeness functions in proverbial discourse.
Keywords: politeness; proverb; discourse; pragmatics